IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK DI KABUPATEN MINAHASA TENGGARA - V. Gosal , Febry; Mokat, , Jetty E. H.; Wawointana, Thelma (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to identify, analyze, and describe the implementation of policies related to information disclosure, particularly regarding information that must be provided and announced periodically by the Department of Communication, Information, Statistics, and Encryption of Minahasa Tenggara Regency. This research employs a qualitative approach. The findings of the study reveal the following: a) Program: In Minahasa Tenggara Regency, despite the mandatory provision of information, the implementation practices face serious challenges, such as unclear procedures for information requests and delays in delivering information to the public; b) SOP: Several obstacles were identified, including unclear information request procedures, delays in response, and misalignment between program implementation and established priorities; c) Human Resources Competence: While the availability of personnel is adequate, not all employees perform their duties in line with their expertise, skills, and abilities, particularly in managing public information; and d) Availability of Facilities and Infrastructure: The resources supporting the implementation of public information disclosure at the Department of Communication, Information, Statistics, and Encryption in Minahasa Tenggara are still highly limited. The main issues include inadequate technological infrastructure, the absence of proper information service facilities, and limited accessibility for people with disabilities.